Practical manual of Neogene Planktonic Foraminifera - IACCARINO, S.; PREMOLI SILVA, I.; BIOLZI, M.; FORESI, L. M.; LIRER, F.; TURCO, E.; PETRIZZO, M. R. (Biolzi M., Iaccarino S.M., Turco E., et al., 2007)
This manual comprises, beside the principles of classification we adopted here, a description sheet for each genus with the major diagnostic features and the list of the selected and more utilized species; the two biostratigraphic zonations and range charts for the subtropical-tropical apen ocean and for the Mediterranean region; a large set of plates illustrating the most important and common Miocene to Holocene taxa as isolated specimens (mostly three views). Taxa are arranged in alphabetical order per genus and per species within genera. Illustrations are generally scanned by previously published papers or atlases, while few of them come from our archives.